Implementation of Restorative Justice By The Police In Handling Children's Theft Crimes In The City Of Sibolga - Perdana A.R Surbakti; Agus Ariadi (Universitas Dehasen Bengkulu, 2026)
The implementation of restorative justice by the police in handling theft crimes in the City of Sibolga is carried out in accordance with the mandate of the Juvenile Criminal Justice System (SPPA) Law, emphasizing the urgency of rehabilitation rather than repressive actions towards children to create social welfare for children as offenders. The purpose of the study is to analyze the implementation of restorative justice by the police in achieving restorative justice for children as perpetrators, victims, and the community, as well as to identify the supporting and inhibiting factors in its implementation. The research method used is qualitative with a case study approach, involving in-depth interviews with police officers, social workers, parents of child offenders, and victims, as well as document analysis related to cases of child theft handled using the restorative justice approach in the City of Sibolga. The results of the study indicate that the implementation of restorative justice by the police in Sibolga City has been carried out, although there are variations in its success rates, as seen from the recurrence of offenses committed by children. Mediation and deliberation to reach an agreement are important parts of this method, allowing dialogue among all parties to find restorative solutions. The level of success highly depends on the willingness of all parties to actively participate, the capabilities of competent facilitators, as well as support from relevant institutions and the broader community. However, there are challenges such as the public's lack of understanding of restorative justice, limited resources, and resistance from some parties, which remain significant obstacles. This research clearly shows that restorative justice provides a good alternative in handling crimes involving children, with the potential to reduce the rate of repeat offenses and support the social well-being of children in the City of Sibolga.